METHODS FOR ASSESSING THE ECONOMIC VIABILITY OF BIOGAS PLANT INVESTMENTS - Milić, Dragan (Journal on Processing and Energy in Agriculture, 2020)
The development of the global economy and booming population growth have resulted in the increased consumption of energy and the growing need for alternative energy sources. This paper presents the use of yield methods for assessing the economic justification of investments in biogas plants, as well as a review of the economic results of biomass energy production, with the aim of determining the present value of future benefits from the electrical and heat energy generated in such plants for fruit drying and processing purposes. The purpose of this paper is to determine the economic viability of investments in renewable energy sources such as biogas plants that can be used effectively in the production and storage of dried fruit. The yield-method results obtained indicate that the production of electrical and heat energy from waste biomass in biogas plants can produce positive financial results.
Keywords: yield value, biogas, biomass, energy